A rough estimation of induction characteristics for geomagnetic variations at Syowa and Iceland - Tsunomura, Satoru (National Institute of Polar Research, 1990)
P(論文) Basic characteristics of geomagnetic induction at Syowa Station are estimated by showing the induction arrows for various types of geomagnetic disturbances using one second values of geomagnetic field. It is found out that satisfactory solutions are obtained for the daytime disturbances. Induction arrows at Iceland are also obtained using the daytime disturbances. At Syowa Station, the induction arrows for the periods longer than several minutes reveal a coast line effect of Lutzow-Holm Bay while island effect is apparent for shorter periods. At Iceland, the coast line effect is dominant at Isafjordur and Tjornes but the induction effects are generally small at Husafell. The induction characteristics obtained here can be referred to as basic relationship in the analyses of geomagnetic phenomena dealing with the vertical component of geomagnetic variations. departmental bulletin paper